(untitled) (Bangladesh Journal of Medical Physics, 2025)
Graves’ disease (GD) accounts for the majority of hyperthyroidism cases worldwide and remains a major diagnostic challenge in settings with limited access to nuclear imaging. Although thyroid-stimulating hormone receptor antibody (TRAb) assay and thyroid scintigraphy are considered diagnostic standards, scintigraphy exposes patients to radiation, is not universally available, and is unsuitable in pregnancy. Color Doppler ultrasonography (CDU) offers a real-time, safe, and accessible alternative for assessing thyroid vascularity through Peak Systolic Velocity (PSV) and Blood Flow Volume (BFV) of the superior thyroid artery (STA). To evaluate the diagnostic accuracy of PSV and BFV of the STA measured by CDU compared with thyroid scintigraphy in TRAb-positive thyrotoxic patients and to determine optimal cut-off values for these indices. This cross-sectional study was conducted at the National Institute of Nuclear Medicine & Allied Sciences (NINMAS), Dhaka, from July 2023 to July 2024. A total of 90 TRAb-positive thyrotoxic patients (40 males, 50 females; mean age 42.9 ± 12.6 years) were included. All patients underwent thyroid scintigraphy with uptake and CDU evaluation of PSV and BFV of the STA. Statistical analysis included independent t-tests and receiver operating characteristic (ROC) curve analysis to determine cut-off values, sensitivity, specificity, predictive values, and diagnostic accuracy. Thyroid scintigraphy confirmed GD in 75 patients (83.3%) and excluded it in 15 (16.7%). Mean PSV (78.6 ± 12.7 cm/s) and BFV (236.0 ± 54.4 ml/min) were significantly higher in GD compared with non-GD patients (p < 0.05). ROC analysis identified cut-off values of 71 cm/s for PSV and 186 ml/min for BFV. PSV demonstrated sensitivity 72.0%, specificity 66.7%, positive predictive value (PPV) 91.5%, and accuracy 71.1%. BFV showed sensitivity 74.7%, specificity 53.3%, PPV 88.9%, and accuracy 71.1%. CDU-derived PSV and BFV of the STA significantly correlate with scintigraphy findings in GD. Given its non-invasiveness, accessibility, and lack of radiation hazard, CDU-particularly BFV—may serve as a reliable alternative diagnostic modality for Graves’ disease. Ban. J. Med. Phys., Vol -16, Issue -1, 2025 : 30-36